Rosalie the Rapunzel fairy - Meadows, Daisy (London : Orchard Books, 2016)
Rachel and Kirsty are having a great time at the Wetherbury Storytelling Festival. But when they come to read the story of Rapunzel, she has long blue hair and an ugly face! Could this be the work of nasty Jack Frost?
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction